“Recently imported from Italy” : : disiecta membra dagli scavi della famiglia Campanari e dalle relative aste sul mercato antiquario londinese - Franceschini, Mariachiara; Pasieka, Paul P. (2023)
Abstract: The activity of the Campanari family, which left its mark on the archaeological landscape of Vulci for years, had mainly, though not exclusively, commercial interests. The dispersion of materials and the market dynamics governing sales are often difficult to trace due to the scarcity of documentation. On the basis of the catalogues of the auctions, which the Campanari family held in London between 1837 and 1841, the antiquarian and commercial practices that linked the family from Tuscania to European collectors and the network of the 19th-century art market, particularly the Anglo-Saxon one, will be discussed. In this way, a rich panorama is obtained not only of the characteristics of the objects traded, but above all of the protagonists of the purchases, their preferences, social class and the various interests that animated them